The defects of private bill legislation - Malley, George Orme (Statistical and Social Inquiry Society of Ireland, 1869)
The great importance of the question of Private Bill Legislation in relation to the growing wants of the community is so vast and so interesting, that it requires no small resolution for anyone, however experienced, to undertake the treatment of the subject. I hope, however, that before an audience like this, the defects in my manner of dealing with it will be received with every indulgence, and my deficiencies atoned for by the motives which have induced me to accept the responsibility.
Read Tuesday, 16th February, 1869
Keywords: Private bill legislation in Ireland; Drainage Acts; 314.15